“Looking over at the Mountains”: Sense of place in the Third Karmapa’s “Songs of Experience” - Gamble, Ruth (Studia Orientalia Electronica, 2015)
The third Karmapa, Rangjung Dorje, was a life-long poet who specialized in the mgur genre of Tibetan folk poetry. By his time, this genre had become particularly associated with the mahāmudra tradition, which placed great emphasis on the metaphoric potential of relative truth. As such, in Rangjung Dorje’s poems, the environment is presented as a catalyst for seeing the enlightened “view” (Tib. lta ba). This paper looks at the metaphorical landscape that Rangjung Dorje’s poems evoke, or, to incorporate a helpful term from contemporary literary studies, their “psychogeography”, their “sense of place”. In doing so, it will explore the relationship between this sense of place and the ‘view’ in respect to his use of the Tibetan word yul, which means both a ‘place’ and an ‘object of the senses’. It will examine, for example, how Rangjung Dorje plays with this term in these poems, using it to link the vast spaces of the Mongolian Empire with the restricted site of his ink evoking them on paper. It will also examine further particulars of his environmental presentation with regards to his privileging of the rural over the environment, and the peripheral “mountain dwellers” over the government’s city dwelling elites.